(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article is devoted to the actual problem of graphic design of digital logic devices. To simulate digital logical devices, logical functions are written for logical variables and, accordingly, diagrams of digital logical devices are created. The paper considers the graphic design of digital logic devices.The subject of the research is the creation of a logical scheme of a numerical logical structure that identifies a team that won first place according to the jury of a programming competition called HACKATON. Since three variables are considered, the logical function is written according to the context of the problem, and a Karnaugh map is used to minimize it. As a result, a minimized function was obtained and a logical circuit of the function was built. According to this scheme, recommendations are given for the construction of various digital logic devices.